Chitosan as a membrane material for pervaporation separation of isopropanol-water mixtures - Hassan, Hashim; Mohd Nawawi, Mohd Ghazali (Penerbit UTM Press, 2008)
Chitosan based pervaporation membranes were prepared from locally available shrimp shells using various chemical treatments. The dried shrimp shells were first grinded and treated with sodium hydroxide aqueous solution and then followed by treating with hydrochloric acid solution to remove the calcium content before chitin is produced. The chitosan membranes were prepared by dissolving a pre-weighed quantity of chitosan into acetic acid solutions. Membranes characteristics and its performance were studied for the pervaporation separation of isopropanolwater mixtures. The homogeneous chitosan membranes showed preferential water sorption and permeation. Results show that the total permeation flux for the homogeneous chitosan membrane decreases while separation increases as the feed isopropanol concentration increases from 10 to 95 wt%. Based on the present study, it is found that the chitosan membranes produced from domestic shrimp shells could be used as the raw material for the production of high water selective membranes.